Optimizing wear rate for PDC cutter using taguchi’s technique and response surface methodology a comparative analysis - Aliff Jamaludin, Amirul; Mizamzul Mehat, Nik; Kamaruddin, Shahrul (International Journal of Engineering and Technology, 2019)
This paper presents the findings of a simulation results on the effects of chamfer angle, back rake angle, side rake angle and diame-ter on polycrystalline diamond compact (PDC) cutter wear rate. Design of experiment techniques, i.e. Taguchi’s technique and re-sponse surface methodology (RSM), have been used to accomplish the objective of the study. L9 orthogonal array and face centered central composite (fc-CCD) design have been used for conducting the experiments. Taguchi’s technique as well as 3D surface plots of RSM revealed that chamfer angle is the most significant factor in minimizing wear followed by back rake angle and side rake angle. The effects of cutter diameter were found to be insignificant compared to other factors. Though both the techniques predict-ed near similar results, RSM technique seems to have an edge over the Taguchi’s technique.